The effectiveness of modified basic life support module on knowledge, attitude, and performance of cardiopulmonary resuscitation among university students - Azizul Fadzli, Wan Jusoh@Ab Rahim; Mohd Nizam, Zahary; Nik Ahmad Shaiffudin, Nik Him; Rosliza, Yahaya (2018)
Introduction: Cardiopulmonary resuscitation is a primary method used in the treatment of sudden cardiac arrest. It is a crucial skill that a healthcare provider and a lay rescuer should acquire to improve the survival and the neurological outcome of out-of-hospital cardiac arrest. Several modules were used to teach cardiopulmonary resuscitation for the healthcare provider and lay rescuer, but no module been developed that could be utilised in both population. Thus, this study aims to investigate the effectiveness of modified cardiopulmonary resuscitation training to knowledge (K), attitude (A), and performance (P) between medical and non-medical university students. Methods: This research was a single experimental study involving a total number of 125 students: 58 for a medical group and 67 for a non-medical group. A modified basic life support module, based on American Heart Association guideline 2015 was delivered to both groups under the same study setting. Pre and post KA scores were assessed using Res-Q questionnaire. The performance was evaluated by resuscitation feedback machine. The KA scores were analysed using repeated measure analysis of variance, and performance was examined using Pearson chi-square. Results: The study showed 64.8% of the participants were able to perform high-quality chest compression. Despite significant differences of sociodemographic background, there was no significant difference on effective chest compression between two groups (p = 0.200). There were also significant improvements in KA scores in both groups after intervention (p < 0.001). Conclusion: The knowledge of cardiopulmonary resuscitation can be delivered to everyone as aspired by our stakeholder to have one qualified cardiopulmonary resuscitation provider in a family. This modified basic life support module is reliably applicable to both healthcare and lay rescuer cardiopulmonary resuscitation training. All rescuers will perform in a similar manner, and this will tremendously reduce the discrepancy in the cardiopulmonary resuscitation qualities. Ultimately, this will improve an out-of-hospital return of spontaneous circulation rate.